UNIVERSIDADES QUE OFERTAM CURSOS EAD NO ESTADO DE SANTA CATARINA: UMA COMPARAÇÂO ENTRE O NÍVEL DE MATURIDADE E O ÍNDICE POTENCIAL DE MATURIDADE - Cleide Tirana Nunes Possamai (Universidade Federal de Santa Catarina, 2017)
By virtue of to its constant evolution, Distance Education has become a subject of intense research, after all the objective of this modality of education is to facilitate access to the population to constant improvement, mainly by the frequent use of new technologies and their modernization, consolidating this way as an option that the population finds to update itself. The aim of this study is to compare the maturity level and the potential maturity index in the educational institutions offering courses in Distance Education in the State of Santa Catarina. To reach this goal, a maturity model adapted to the characteristics of this segment was used. Through a quantitative, described, cross-sectional and survey method, data from this study were obtained. The treatment of these data was achieved through fashion. The tabulation was done to identify the Level of Maturity and the Potential Maturity Index of each higher education institution seeking to make the proper comparison. The research findings show the level of maturity and the potential maturity index of each institution of higher education, as well as the comparison between both to verify if there is a level of maturity that is ideal for the Universities of Santa Catarina that offer courses in Distance Education.